A comparative study of the electrical characteristics of metal-semiconductor-metal (MSM) photodiodes based on gan grown on silicon. - Y, C.Lee; Z., Hassan; F., K. Yam; Abdullah, M. J.; Ibrahim, K. (Universiti Sains Malaysia, 2000)

(untitled)
High quality Gan films are usually produced at high growth temperatures (> 1OOO°C) with the use of substrates such as sapphire (Ah03) or silicon carbide (SiC).Therefore, for a low production cost purpose, there has been a growing interest in producing lower growth temperatures Gan films as well as Gan based devices with low cost substrates such as silicon.